Pretreatment with anti-thymocyte globulin versus no anti-thymocyte globulin in patients with haematological malignancies undergoing haemopoietic cell transplantation from unrelated donors: a randomised, controlled, open-label, phase 3, multicentre trial. Issue 2 (February 2016) - Walker, Irwin; Panzarella, Tony; Couban, Stephen; Couture, Felix; Devins, Gerald; Elemary, Mohamed; Gallagher, Geneviève; Kerr, Holly; Kuruvilla, John; Lee, Stephanie J; Moore, John; Nevill, Thomas; et al.
Summary: Background: Pretreatment with anti-thymocyte globulin (ATG) decreases the occurrence of chronic graft-versus-host disease (CGVHD) after haemopoietic cell transplantation from an unrelated donor, but evidence of patient benefit is absent. We did a study to test whether ATG provides patient benefit, particularly in reducing the need for long-term immunosuppressive treatment after transplantation. Methods: We did a phase 3, multicentre, open-label, randomised controlled trial at ten transplant centres in Canada and one in Australia. Eligible patients were aged 16 to 70 years with any haematological malignancy and a Karnofsky score of at least 60 receiving either myeloablative or non-myeloablative (or reduced intensity) conditioning preparative regimens before haemopoietic cell transplantation from an unrelated donor. We allocated patients first by simple randomisation (1:1), then by a minimisation method, to either pretransplantation rabbit ATG plus standard GVHD prophylaxis (ATG group) or standard GVHD prophylaxis alone (no ATG group). We gave a total dose of ATG of 4·5 mg/kg intravenously over 3 days (0·5 mg/kg 2 days before transplantation, 2·0 mg/kg 1 day before, and 2·0 mg/kg 1 day after). The primary endpoint was freedom from all systemic immunosuppressive drugs without resumption up to 12 months after transplantation. Analysis was based on a modified intention-to-treat method. This trial was registered at ISRCTN, number 29899028. Findings: Between June 9, 2010, and July 8, 2013, we recruited and assigned 203 eligible patients to treatment (101 to ATG and 102 to no ATG). 37 (37%) of 99 patients who received ATG were free from immunosuppressive treatment at 12 months compared with 16 (16%) of 97 who received no ATG (adjusted odds ratio 4·25 [95% CI 1·87–9·67]; p=0·00060. The occurrence of serious adverse events (Common Terminology Criteria grades 4 or 5) did not differ between the treatment groups (34 [34%] of 99 patients in the ATG group vs 41 [42%] of 97 in the no ATG group). Epstein-Barr virus reactivation was substantially more common in patients who received ATG (20 [one of whom died—the only death due to an adverse event]) versus those who did not receive ATG (two [no deaths]). No deaths were attributable to ATG. Interpretation: ATG should be added to myeloblative and non-myeloblative preparative regimens for haemopoietic cell transplantation when using unrelated donors. The benefits of decreases in steroid use are clinically significant. Epstein-Barr virus reactivation is increased, but is manageable by prospective monitoring and the use of rituximab. Future trials could determine whether the doses of ATG used in this trial are optimum, and could also provide additional evidence of a low relapse rate after non-myeloablative regimens. Funding: The Canadian Institutes of Health Research and Sanofi.